FAKTOR YANG MEMPENGARUHI KINERJA PERAWAT DALAM PENERAPAN PROSES KEPERAWATAN DI RSUD TOTO KABUPATEN BONE BOLANGO - Buheli, Kartin (Sainstek, 2012)
This research aim to analyse factor influencing nurse performance in applying of treatment process [in] RSUD Toto Sub-Province of Bone Bolango. this Type Research is analytic research [of] observasional with method " study sectional cross" meant to study dynamics of variable which included in research title " Factor Influencing Performance Nurse in Applying Of Process Treatment". Amount of responders counted 51 people as nurse of executor [in] room take care of to lodge. Research result indicate that : nurse have enough motivation counted 45,1 % from 51 responder, earnings / enough salary counted 51 %, nurse owning enough supervision counted 62,7 %, development of enough career counted 45,1% and motivation is strongest factor [of] influence of to nurse performance at home [Common/ Public] Pain [of] Area of Toto Sub-Province of Bone Bolango Provinsi Gorontalo. Result Research can be concluded that nurse performance in applying of treatment process can influence by some factor that is motivations, development of career, earnings and supervise / salary. Is for that suggested [by] the importance of improvement of nurse performance in applying of treatment process [pass/through] support of related/relevant government by budget allocation to nurse service in documentation process treatment and also perform [a] training to commisioned nurse at home Pain, so that service of more maximal treatment and can give satisfaction to society.